1998
DOI: 10.1016/s0002-9440(10)65629-5
|View full text |Cite
|
Sign up to set email alerts
|

ALK Expression Defines a Distinct Group of T/Null Lymphomas (“ALK Lymphomas”) with a Wide Morphological Spectrum

Abstract: The t(2;5)(p23;q35) translocation associated with CD30-positive anaplastic large cell lymphoma results in the production of a NPM-ALK chimeric protein, consisting of the N-terminal portion of the NPM protein joined to the entire cytoplasmic domain of the neural receptor tyrosine kinase ALK. The ALK gene products were identified in paraffm sections by using a new anti-ALK (cytoplasmic portion) monoclonal antibody (ALKc) that tends to react more strongly than a previously described ALK1 antibody with the nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
164
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 249 publications
(180 citation statements)
references
References 48 publications
11
164
1
4
Order By: Relevance
“…Previous studies, in anaplastic large-cell lymphoma, have shown that cellular sublocalization patterns, for the various ALK fusion oncoproteins, are consistent and distinctive. [25][26][27] In some cases, eg, NPM-ALK, a characteristic localization results from shuttling of fusion oncoprotein heterodimers to those cellular structures with which the ALK fusion partner is normally associated. 28 The subcellular localization patterns establish morphological signatures for the different ALK fusion proteins, notwithstanding the fact that the major site of oncogenic action-at least with respect to activation of ALK signaling pathways-is undoubtedly cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, in anaplastic large-cell lymphoma, have shown that cellular sublocalization patterns, for the various ALK fusion oncoproteins, are consistent and distinctive. [25][26][27] In some cases, eg, NPM-ALK, a characteristic localization results from shuttling of fusion oncoprotein heterodimers to those cellular structures with which the ALK fusion partner is normally associated. 28 The subcellular localization patterns establish morphological signatures for the different ALK fusion proteins, notwithstanding the fact that the major site of oncogenic action-at least with respect to activation of ALK signaling pathways-is undoubtedly cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Rho GTPases was first studied in two NPM-ALK positive ALCL cell lines, Karpas 299 (common type) and Cost (small cells, aggressive variant) (Falini et al, 1998;Lamant et al, 2004). Pull-down assays demonstrated that Rac1 was strongly activated in both cell lines (Figure 1a).…”
Section: Npm-alk Activates the Gtpase Rac1 Via Pi3k And Srcmentioning
confidence: 99%
“…The ALK1 and ALKc (Falini et al, 1998) mAbs, which recognize the intracellular, kinasecontaining region of ALK, have been described previously. The anti-Fas (CD95, clone CH11) and anti-phosphotyrosine (clone 4G10) mAbs were purchased from Upstate Biotechnology (Lake Placid, NY, USA), anti-actin mAb (clone AC-10) from Sigma, anti-cytochrome c mAb from Pharmingen (San Diego, CA, USA), anti-cytochrome oxidase subunit II mAb from Molecular Probes (Eugene, OR, USA), polyclonal rabbit anti-human phosphorylated Akt (serine 473) antibody from New England Biolabs (Beverly, MA, USA), and peroxidase-conjugated rabbit anti-mouse and pig anti-rabbit Ig antisera from Dako (Glostrup, Denmark).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Cells were cytospun onto glass slides coated with silane, ®xed in acetone for 10 min, and stained using ALK1 or ALKc (Falini et al, 1998) mAb in a three stage immunoperoxidase technique (Benharroch et al, 1998).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%